The Role of Foreign Investment and Domestic Investment in Indonesia's Gross Domestic Product (GDP) - David Kaluge; Titin juniarti; Sudarnice Sudarnice (Politeknik Baubau, 2025)
This research is important to provide a clear picture of Indonesia's economic dynamics and to support better decision-making in economic policy. Increased domestic investment is not enough to drive overall economic growth, and foreign investment is also not in line with the increase in domestic investment due to a mismatch between domestic investment and expected economic growth outcomes. The purpose of this study is to analyze the role of foreign investment and domestic investment on Indonesia's Gross Domestic Product (GDP). This study uses time series data from 2014-2023. The results of this study indicate that Foreign Direct Investment (FDI) does not have a significant positive effect on Indonesia's Gross Domestic Product (GDP). Although it shows a positive direction, the effect is not significant, so increasing foreign investment is still needed to drive the growth of Indonesia's Gross Domestic Product (GDP). Domestic Direct Investment (DDI) has a significant positive effect on Indonesia's Gross Domestic Product (GDP). This indicates that PMDN significantly contributes to GDP growth in Indonesia, with a stronger role than foreign investment. Simultaneously, foreign investment and domestic investment had a positive and significant impact on Indonesia's Gross Domestic Product (GDP) from 2014 to 2023. This indicates that although domestic investment had a partial negative impact, both simultaneously still made a positive contribution to economic growth.